The thrilling adventure hour - Acker, Ben; Blacker, Ben; Rauch, John; Wallace, Maurício (BOOM! Studios, 2018)
Meet Frank and Sadie Doyle, toast of the upper crust. Headliners on the society pages. And, oh yes, they see ghosts. Trading quips and tossing back cocktails, the Doyles take what they want and hoodwink their clientele for the rest. Ghosts, vampires, werewolves, mummies, even diabolical gingerbread men are nothing but obstacles in the way of the liquor cabinet for our fast-talking, hard-drinking sleuths.